(untitled) (Journal of Engineering, 2009)
The satellite image is multi band image,the first three bands have the largest wavelength and image information and usually contain noise due to different reason such as image band acquisition or transmission. In this paper an adaptive method implemented to denoising the satellite image by using the Haar wavelet transform applied to the principle components bands of the satellite image. The image denoising by Haar wavelet transform is applied on the first band(PC1).This band has found contain about 90% of the image information, in this case the time required for processing and storage size are reduced ,and the image appearance are more suitable than the processing the image bands directily.